Comparison of Predicted Exercise Capacity Equations and the Effect of Actual versus Ideal Body Weight among Subjects Undergoing Cardiopulmonary Exercise Testing - H. Reza Ahmadian; Joseph J. Sclafani; Ethan E. Emmons; Michael J. Morris; Kenneth M. Leclerc; Ahmad M. Slim (Cardiology Research and Practice)
Background. Oxygen uptake at maximal exercise (VO2 max) is considered the best available index for assessment of exercise capacity. The purpose of this study is to determine if the use of actual versus ideal body weight in standard regression equations for predicted VO2 max results in differences in predicted VO2 max. Methods. This is a retrospective chart review of patients who were predominantly in active military duty with complaints of dyspnea or exercise tolerance and who underwent cardiopulmonary exercise testing (CPET) from 2007 to 2009. Results. A total of 230 subjects completed CPET on a bicycle ergometer with a male predominance (62%) and an average age of 37 ± 15 years. There was significant discordance between the measured VO2 max and predicted VO2 max when measured by the Hansen and Wasserman reference equations (P<0.001). Specifically, there was less overestimation when predicted VO2 max was based on ideal body weight as opposed to actual body weight. Conclusion. Our retrospective analysis confirmed the wide variations in predicted versus measured VO2 max based on varying prediction equations and showed the potential advantage of using ideal body weight as opposed to actual body weight in order to further standardize reference norms.